Alcance de la S.A.S. en el derecho societario a la luz del principio de la libertad contractual. - Ortiz Cano, María Isabel (Revista Pensamiento Americano)
This article analyzes the incentives and legal obstacles content by the Law 1258 of 2008 by which it is created in the legal system the S.A.S, law in which most of its provisions are supplementary and a minimum amount is mandatory. For this, the regulation of this type of scope is contrasted with the other company vehicles of the Commercial Code that are still valid, having as its axis the principle of contractual liberty and its historical development in corporate rights. Additionally, the article measures the scopes of the S.A.S in Colombia's legislation with a little more of a decade validity.